2022
DOI: 10.3390/ma15217588
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductance of Copper–Graphene Interface: A Molecular Simulation

Abstract: Copper is often used as a heat-dissipating material due to its high thermal conductivity. In order to improve its heat dissipation performance, one of the feasible methods is to compound copper with appropriate reinforcing phases. With excellent thermal properties, graphene has become an ideal reinforcing phase and displays great application prospects in metal matrix composites. However, systematic theoretical research is lacking on the thermal conductivity of the copper–graphene interface and associated affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…This behavior can be explained by the fact that the graphene-copper interfaces act as defects that dissipate heat when encountered. A study [42] delved into the impact of an increasing number of graphene layers on the thermal conductivity of the interface, which aligns with our findings. As the number of graphene layers in the crystal increases, the number of defects also increases, and it is natural that the thermal conductivity will deteriorate.…”
Section: Resultssupporting
confidence: 87%
“…This behavior can be explained by the fact that the graphene-copper interfaces act as defects that dissipate heat when encountered. A study [42] delved into the impact of an increasing number of graphene layers on the thermal conductivity of the interface, which aligns with our findings. As the number of graphene layers in the crystal increases, the number of defects also increases, and it is natural that the thermal conductivity will deteriorate.…”
Section: Resultssupporting
confidence: 87%
“…39 The computed result of decreasing interfacial thermal conductance of the CoSb 3 -graphene system with the increasing number of graphene layers is in an agreement with that of the gold-graphene and copper-graphene system. 36,40 The interfacial thermal conductance decreased with an increase in the number of graphene layers and converged when the number of graphene layers exceeded a certain value.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating graphene with metals can mitigate performance losses and failure in thermal applications [10,11]. Among metals, due to copper having excellent electrical and thermal properties and being inexpensive, it has long been extensively used since it is one of the best metallic, electrical, and thermally conductive materials [12][13][14]. Moreover, nano-scaled copper is used inside electronic devices such as computers and wearable technological equipment for faster data transmission, efficient energy distribution, and current flow in next-generation conductors and chips.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to graphene's contribution to the structure's shape, the results showed that structural rearrangement significantly improves the strength and durability of the nanocomposites. The interfacial thermal conductivity of copper-graphene using the non-equilibrium molecular dynamics (NEMD) simulations method was studied to investigate the effects of graphene, sizes, and vacancy rate [14]. They obtained that the interfacial thermal conductivity decreases with the number of graphene and increases with the defect density of graphene up to 3.5%.…”
Section: Introductionmentioning
confidence: 99%